Relationship between Perception with Nurse Anxiety Level about Covid-19 at RSU Karsa Husada Batu - Dini Yulianti; Rahmawati Maulidia; Achmad Dafir Firdaus (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
The incidence of Covid-19 cases continues to increase from day to day so that health workers as the front line are increasingly stressed due to the increasing workload, worrying about their health, and families who have an impact on health workers will experience increased anxiety. The perception of health workers about COVID-19 is closely related to the level of anxiety. A positive perception of a disease will experience mild anxiety. A negative perception of a disease can also make the level of anxiety higher. The purpose of this study was to determine the relationship between perception and level of anxiety. The research design is quantitative analytic with a cross-sectional approach. Sampling using purposive sampling with a sample of 65 respondents. Data analysis using Pearson product moment correlation test. The results showed the significance value of perception with anxiety level was 0.084 (> 0.05). The results showed that there was no relationship between the perceptions of nurses at Karsa Husada Batu General Hospital about Covid-19 and anxiety. This is supported by nurses' perceptions of Covid-19 being in the moderate category, while nurses' anxiety about Covid-19 is in the moderate category. This means that nurses perceive Covid-19 as a flu that does not need to be feared. In addition, the high level of education and knowledge of nurses, the experience of nurses, the readiness of the Karsa Husada Batu Hospital in facing the maximum Covid-19 pandemic in the form of the application of 3M, the availability of adequate PPE greatly affects the perception and anxiety of nurses about COVID-19. For further researchers, it is hoped that they can conduct further research on the factors that can affect anxiety about Covid-19. It is also necessary to do similar research with other variables with additional measurements.